2015
DOI: 10.1111/cdev.12455
|View full text |Cite
|
Sign up to set email alerts
|

Parental Perceptions of Aggressive Behavior in Preschoolers: Inhibitory Control Moderates the Association With Negative Emotionality

Abstract: Inhibitory control (IC) and negative emotionality (NE) are both linked to aggressive behavior, but their interplay has not yet been clarified. This study examines different NE × IC interaction models in relation to aggressive behavior in 855 preschoolers (aged 2-5 years) using parental questionnaires. Hierarchical regression analyses revealed that NE and IC predict aggression both directly and interactively. The highest aggression levels were reported in children with high NE and low IC. Interestingly, the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 54 publications
1
25
1
Order By: Relevance
“…These include the ability to withhold a pre-potent response, use working memory to deploy behavior flexibly in complex scenarios, or register and change stimulus-response mappings after making an error. In fact, an extensive literature links pediatric aggression to these and other components of cognitive control [5558]. While these studies generally do not differentiate reactive from proactive aggression, one study did find a specific association between reactive aggression and deficits in sustained attention and set-shifting [59].…”
Section: Reward Processing In Irritable Youthmentioning
confidence: 99%
“…These include the ability to withhold a pre-potent response, use working memory to deploy behavior flexibly in complex scenarios, or register and change stimulus-response mappings after making an error. In fact, an extensive literature links pediatric aggression to these and other components of cognitive control [5558]. While these studies generally do not differentiate reactive from proactive aggression, one study did find a specific association between reactive aggression and deficits in sustained attention and set-shifting [59].…”
Section: Reward Processing In Irritable Youthmentioning
confidence: 99%
“…Specifically, using maternal reports, Suurland et al. () found that a lack of inhibitory control was predictive of aggressive behavior during preschool, especially in children showing high negative temperamental reactivity. Utendale and Hastings () reported that lower maternally reported inhibitory control was related to more externalizing behavior observed during a play task with other children in 3‐ to 6‐year‐olds, and both Raaijmakers et al.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Vuontela et al (2013) in a sample of children aged between 7 and 12 years, found that lower levels of inhibitory control were related to higher externalizing symptoms, as reported by their parents. Other studies with preschoolers (Raaijmakers et al, 2008; Suurland et al, 2016) have shown that higher levels of aggression were related to lower inhibitory control. These results are also consistent with the findings of other studies in adolescents.…”
Section: Discussionmentioning
confidence: 86%
“…Thus, lower levels of parental education are related to higher levels of aggressive behavior through lower inhibitory control, which is consistent with our second hypothesis. Inhibitory control has been demonstrated to be a moderator and mediator variable in a wide range of outcomes (Pardini et al, 2004; Runions and Keating, 2010; Merz et al, 2014; Suurland et al, 2016). However, to the best of our knowledge, this is the first study analyzing this mediation effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation